PEMAHAMAN KARUNIA-KARUNIA ROH KUDUS TERHADAP KUALITAS KEROHANIAN JEMAAT - Yoseph Renaldi; Ragil Kristiawan; Didasgil S.I Taneo (STT Kristus Alfa Omega, 2023)
The study was conducted to learn how much the congregation understands the gifts of the Holy Spirit, the level of spiritual quality of the congregation, and the extent of understanding of the gifts of the Holy Spirit have on spiritual qualities. After researchers had done extensive research, congregation understanding had a value of 88% in an excellent category, the congregation's level of spiritual quality of 69% in good category, and the influence of understanding of the gifts of the Holy Spirit on a congregation's spiritual quality had a strong value of 0.742.